KAJIAN PENINGKATAN PENGETAHUAN FITOFARMAKA UNTUK SWAMEDIKASI PADA TIM PENGGERAK PKK DI SURAKARTA: A STUDY ON IMPROVING PHYTOPHARMACA KNOWLEDGE FOR SELF-MEDICATION IN THE PKK MOBILIZATION TEAM IN SURAKARTA - Pambudi, Risma Sakti; Khusna, Khotimatul; Safitri, Desti Anggi; Windiasari, Farah Puteri (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2024)
Public knowledge related to the use of traditional medicine is still low and does not know other traditional medicine classes such as OHT (Standardized Herbal Medicine) and phytopharmaca groups. The purpose of this study was to determine the level of knowledge of the use of phytopharmaca for self-medication in the PKK team of Surakarta city. The method in this study used quantitative research with a quasi experimental design with one group pre and post test design. The pre-test was used at the time of the delivery of the material with the aim of knowing the extent to which the material was understood by the respondents. While the post-test is carried out at the end of the material treatment process with the aim of knowing the extent of understanding of the material provided. Analyze respondents' knowledge by looking at the formula to measure the percentage of answers obtained from the questionnaire. The results showed the level of knowledge of respondents during the pre-test, namely having good knowledge (39.22%), sufficient knowledge (48.04%) and less (12.75%). After being given treatment, respondents filled out a questionnaire and obtained a value for the post-test knowledge level, namely good (63.73%), sufficient (30.39%), and less (12.75%). The results showed that there was a difference in the pre and post test scores of respondents after being treated with a sig value (2-tailed) of 0.000, which is <0.05. The conclusion of this study is that there is an average difference between pre and post and there is an effect with a sig value of 0.000, which is <0.05. Keywords: Medicine, Phytopharmaca, Knowledge, Self-medication, Surakarta